KANDUNGAN ANTIOKSIDAN BEBERAPA LALAPAN - Amril Latif (Jurnal Matematika Sains dan Teknologi, 2006)
The product of fat oxidation on food has a significant effect towards human’s health, especially those who often consume it. It has been known for long time that vegetables, fruits, and fish have an ability to stifle Free Radical through the activities of antioxidant belonged to them. Among some kinds of antioxidant, natural antioxidant is the one which does not have any side-effects. This research is aimed to know the ability of antioxidant consisted in kemangi leaves, kemangi, rende, poh-pohan, and lettuce to stifle Free Radical. Based on the result of spectrophotometer test towards those dishes of raw vegetables (lalapan), kemang leaves have the most antioxidant with 0,488 absorption, followed by rende leaves with 0,394 absorption, kemangi leaves with 0,326 absorption, poh-pohan leaves with 0,176 absorption, and lettuce with 0,1635 absorption. Based on the spectrum analysis, it can be seen that lettuce leaves have more effective antioxidant to stifle Free Radical.